Hak Ahli Waris Keturunan Raja Dalam Persekutuan Ratschaap Yarbadang - Mussad, Saini; Matuankotta, Jenny Kristiana; Latupono, Barzah (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Inheritance law is a legal regulation that regulates inheritance due to death, the formulation of silent words until someone dies and causes inheritance problems, the death of this person is a legal event. Each Ratschaap belongs to one of the three major alliances, namely Ur siu (clump of nine), Loor lim (clump of five) and Loor labia (clump of intermediate) it is recorded that ten Ratschaap are members of Ur siu, the next ten Ratschaap are joined in Loor lim and the remaining two Ratschaap belonging to the Loor labia.Purposes of the Research: The purpose of this study is to examine the normative juridical regarding the rights of the heirs of the king's descendants in the Ratschaap Yarbadang Alliance in Southeast Maluku with theories and facts that occur in the social community of Southeast Maluku.Methods of the Research: In this legal research, the author uses empirical juridical research where this study uses a sociological research problem approach using original data using an empirical approach to knowledge based on facts from research results and observations according to this legal research.Results of the Research: The results of this study indicate, Article 18b paragraph (2), the 1945 Constitution of the Republic of Indonesia and the Village Law Number 06 of 2014 as well as the Southeast Maluku Regency Government Regulation Number 04 of 2009 concerning Procedures for Nomination, Election and Inauguration of Heads. The government of Ohoi/Ohoi Rat, has regulated and given rights to the entire community of Southeast Maluku in exercising their customary and cultural rights, as well as parties who are not responsible for ancestral customs.